Dual conformational recognition by Z-DNA binding protein is important for the B–Z transition process - Park, Chaehee (Nucleic Acids Res, 2020)
Left-handed Z-DNA is radically different from the most common right-handed B-DNA and can be stabilized by interactions with the Zα domain, which is found in a group of proteins, such as human ADAR1 and viral E3L proteins. It is well-known that most Zα domains bind to Z-DNA in a conformation-specific manner and induce rapid B–Z transition in physiological conditions. Although many structural and biochemical studies have identified the detailed interactions between the Zα domain and Z-DNA, little is known about the molecular basis of the B–Z transition process. In this study, we successfully converted the B–Z transition-defective Zα domain, vvZα(E3L), into a B–Z converter by improving B-DNA binding ability, suggesting that B-DNA binding is involved in the B–Z transition. In addition, we engineered the canonical B-DNA binding protein GH5 into a Zα-like protein having both Z-DNA binding and B–Z transition activities by introducing Z-DNA interacting residues. Crystal structures of these mutants of vvZα(E3L) and GH5 complexed with Z-DNA confirmed the significance of conserved Z-DNA binding interactions. Altogether, our results provide molecular insight into how Zα domains obtain unusual conformational specificity and induce the B–Z transition.